Effectiveness of Dementia Care Mapping™ to reduce agitation in care home residents with dementia: an open-cohort cluster randomised controlled trial. (3rd August 2021) - Surr, Claire A.; Holloway, Ivana; Walwyn, Rebecca E. A.; Griffiths, Alys W.; Meads, David; Martin, Adam; Kelley, Rachael; Ballard, Clive; Fossey, Jane; Burnley, Natasha; Chenoweth, Lynn; Creese, Byron; et al.
Abstract: Objectives: Agitation is common and problematic in care home residents with dementia. This study investigated the (cost)effectiveness of Dementia Care Mapping™ (DCM) for reducing agitation in this population. Method: Pragmatic, cluster randomised controlled trial with cost-effectiveness analysis in 50 care homes, follow-up at 6 and 16 months and stratified randomisation to intervention ( n = 31) and control ( n = 19). Residents with dementia were recruited at baseline ( n = 726) and 16 months ( n = 261). Clusters were not blinded to allocation. Three DCM cycles were scheduled, delivered by two trained staff per home. Cycle one was supported by an external DCM expert. Agitation (Cohen-Mansfield Agitation Inventory (CMAI)) at 16 months was the primary outcome. Results: DCM was not superior to control on any outcomes (cross-sectional sample n = 675: 287 control, 388 intervention). The adjusted mean CMAI score difference was –2.11 points (95% CI –4.66 to 0.44, p = 0.104, adjusted ICC control = 0, intervention 0.001). Sensitivity analyses supported the primary analysis. Incremental cost per unit improvement in CMAI and QALYs (intervention vs control) on closed-cohort baseline recruited sample ( n = 726, 418 intervention, 308 control) was £289 and £60, 627 respectively. Loss to follow-up at 16 months in the original cohort was 312/726 (43·0%) mainly (87·2%) due to deaths. Intervention dose was low with only a quarter of homes completing more than one DCM cycle. Conclusion: No benefits of DCM were evidenced. Low intervention dose indicates standard care homes may be insufficiently resourced to implement DCM. Alternative models of implementation, or other approaches to reducing agitation should be considered.